Chemical Composition, Antibacterial, Schistosomicidal, and Cytotoxic Activities of the Essential Oil of Dysphania ambrosioides (L.) Mosyakin & Clemants (Chenopodiaceae). Issue 8 (29th July 2017) - Soares, Marina H.; Dias, Herbert J.; Vieira, Tatiana M.; de Souza, Maria G. M.; Cruz, Ana F. F.; Badoco, Fernanda R.; Nicolella, Heloiza D.; Cunha, Wilson R.; Groppo, Milton; Martins, Carlos H. G.; Tavares, Denise C.; Magalhães, Lizandra G.; et al.
Abstract : We have investigated the chemical composition and the antibacterial activity of the essential oil of Dysphania ambrosioides (L.)Mosyakin &Clemants (Chenopodiaceae) (DA‐EO) against a representative panel of cariogenic bacteria. We have also assessed the in vitro schistosomicidal effects of DA‐EO on Schistosoma mansoni and its cytotoxicity to GM07492‐A cells in vitro . Gas chromatography (GC) and gas chromatography‐mass spectrometry (GC/MS) revealed that the monoterpenes cis ‐piperitone oxide (35.2%), p ‐cymene (14.5%), isoascaridole (14.1%), and α ‐terpinene (11.6%) were identified by as the major constituents of DA‐EO. DA‐EO displayed weak activity against Streptococcus sobrinus and Enterococcus faecalis (minimum inhibitory concentration ( MIC ) = 1000 μg/ml). On the other hand, DA‐EO at 25 and 12.5 μg/ml presented remarkable schistosomicidal action in vitro and killed 100% of adult worm pairs within 24 and 72 h, respectively. The LC 50 values of DA‐EO were 6.50 ± 0.38, 3.66 ± 1.06, and 3.65 ± 0.76 μg/ml at 24, 48, and 72 h, respectively. However, DA‐EO at concentrations higher than 312.5 μg/ml significantly reduced the viability of GM07492‐A cells ( IC 50  = 207.1 ± 4.4 μg/ml). The selectivity index showed that DA‐EO was 31.8 times more toxic to the adult S. mansoni worms than GM07492‐A cells. Taken together, these results demonstrate the promising schistosomicidal potential of the essential oil of Dysphania ambrosioides . Abstract :